Package ‘springer’ - Zhou, Fei; Liu, Yuwen; Lu, Xi; Ren, Jie; Wu, Cen (My University, 2023)
Recently, regularized variable selection has emerged as a powerful tool to iden- tify and dissect gene-environment interactions. Nevertheless, in longitudinal studies with high di- mensional genetic factors, regularization methods for G×E interactions have not been systemati- cally developed. In this package, we provide the implementation of sparse group variable selec- tion, based on both the quadratic inference function (QIF) and generalized estimating equa- tion (GEE), to accommodate the bi-level selection for longitudinal G×E studies with high dimen- sional genomic features. Alternative methods conducting only the group or individual level se- lection have also been included. The core modules of the package have been developed in C++.
Sparse Group Variable Selection for Gene-Environment Interactions in the Longitudinal Stud